Fatigue and exhaustion in hypoxia: The role of cerebral oxygenation - Fan, J. L.; Kayser, B. (High Altitude Medicine & Biology, 2016)
It is well established that ascent to high altitude is detrimental to one's aerobic capacity and exercise performance. However, despite more than a century of research on the effects of hypoxia on exercise performance, the underlying mechanisms remain incompletely understood. While the cessation of exercise, or the reduction of its intensity, at exhaustion, implies reduced motor recruitment by the central nervous system, the mechanisms leading up to this muscular derecruitment remain elusive. During exercise in normoxia and moderate hypoxia (~1500-2500 m), peripheral fatigue and activation of muscle afferents probably play a major role in limiting exercise performance. Meanwhile, studies suggested that cerebral tissue deoxygenation may play a pivotal role in impairing aerobic capacity during exercise in more severe hypoxic conditions (~4500-6000 m). However, recent studies using end-tidal CO2 clamping, to improve cerebral tissue oxygenation during exercise in hypoxia, failed to demonstrate an improvement in exercise performance. In light of these recent findings, which seem to contradict the hypothetical role of cerebral tissue deoxygenation as a performance limiting factor at high altitude, this short review aims to provide a critical reappraisal of the extant literature and ends exploring some potential avenues for further research in this field.